Brazilian Education System: universities of excellence in light of national academic rankings (Práxis Educativa, 2024)
The article aims to analyze comparatively the historical evolution that Brazilian universities have had in the three main national rankings: University Ranking Universitario Folha, Guia do Estudante and the ranking generated by the Ministry of Education, the General Course Index (IGC). For this, a bibliographic and documentary analysis of secondary sources of information was carried out. In general, it was detected: (1) there is a set of institutions that are always located in a certain range of positions, regardless of the ranking, the methodology used or the year in question, most of which are public, only two are private, but denominational, philanthropic and non-profit; (2) In Brazil, in a universe of 203 universities, there is a select group of excellence made up of only 13 universities, according to the criteria of the three rankings analyzed.Keywords: Higher Education. University governance. Quality indicators.